Pengembangan Aplikasi Reservasi Penginapan dan Sewa Kendaraan Berbasis Android Kotlin dengan Metode Rapid Application Development - Fatih Ahmad Zakaria; Arif Pramudwiatmoko (METIK JURNAL, 2024)
The tourism industry in Indonesia continues to grow with the increasing interest of tourists in destinations offering authentic experiences. One of the challenges in this industry is the need for a fast and efficient reservation system, particularly for homestays, which are becoming increasingly popular. This study aims to develop an Android-based reservation application for accommodation and vehicle rentals using the Rapid Application Development (RAD) method. The application is designed to provide convenience for tourists in booking accommodations and vehicles, as well as providing information on attractions around the accommodation. Additionally, a web-based admin dashboard was developed for administrators to manage reservation data more efficiently. The RAD method was chosen because it can accelerate the development process by going through the planning, design, construction, and cutover stages. The results from testing using the Black Box technique show that the application functions as expected. The application successfully implements features for reservations, vehicle rentals, and nearby attraction information, while integrating the Midtrans Payment Gateway to facilitate transaction processes.